Dialysis in Critically Ill Patients with Hypokalemia: A Challenge to Beat by Adjusting Potassium Bath in Dialysate : Hypokalemia Management in Critically Ill Dialysis Patients - Bibi, Shaheen; Qayyum, Sumiya; Hussain, Iqbal; Khan, Sundus (Pakistan Journal of Health Sciences, 2024)
Acute renal injury (ARI) is common in critically ill patients and frequently makes renal replacement therapy necessary. Low serum potassium level is associated with arrhythmias and mortality in critically ill patients. Adjusting dialysate fluid potassium to higher level helps preventing post hemodialysis hypokalemia. Objective: To establish role of high potassium dialysate in management of hypokalemia in critically ill patients undergoing renal replacement therapy for ARI. Methods: We did a pilot study and performed a cohort on critically ill patients who developed acute renal injury and required renal replacement therapy for acute indications. We designed two groups each consisting 50 patients. Control group underwent hemodialysis with conventional dialysate. For interventional group, we added potassium bath of 3.0meq/l. Pre and post hemodialysis serum potassium levels were measured results mentioned in the form of bar chart. Results: For intervention group mean pre and post hemodialysis serum potassium levels were 3.43±0.36mg/dl and 4.45±5.00mg/dl respectively with no statistically significant difference in pre and post hemodialysis potassium (p=0.156). While, for control group mean pre and post hemodialysis serum potassium levels were 3.69±0.38mg/dl and 2.97±0.29mg/dl respectively. Difference in pre-post mean serum potassium in control group was statistically significant (p<0.001). Furthermore, three patients in control group developed atrial fibrillation in which hypokalemia was confirmed by laboratory testing. Conclusions: Acute dialysis in critical care on hypokalemic patients can be performed safely by adjusting potassium bath in dialysate.